Pengembangan Strategi Social Media Marketing Untuk Mengingkatkan Keanggotaan UMKM Di Kadin Bali - Dewi, Kamiaa Raesita (Universitas Katolik Soegijapranata, 2024)
The Chamber of Commerce and Industry (KADIN) is a government organization that houses all Indonesian entrepreneurs within the scope of state, private and cooperative businesses. The Chamber of Commerce and Industry is a bridge in several processes, ranging from the process of coaching to advocating Indonesian entrepreneurs. In increasing the excellence of the Indonesian business world, the development of national resources must be carried out in a balanced manner to build a strong market economy order. In this service, the writer uses the Participatory Action Research (PAR) method by going through three stages, namely the planning, implementation and observation stages. With the existence of social media marketing, the membership of MKM Kadin Bali has increased from time to time.